The Influence of Customer Orientation and Social Media Utilization on MSMe Performance Growth - Komariyah, Imas; Takhyudin, Yusup; Hidayat, Wahyu; Suhardi, Tedi (Journal of Management, 2024)
This study aims to explore the influence of Customer Orientation and Media Adoption on SME Performance. This study uses a quantitative approach by collecting data from 100 SME respondents in Indonesia. The results showed that Customer Orientation has a significant and positive relationship with SME Performance (r = 0.687, p < 0.01) and proved to be a significant predictor in the regression model (B = 0.387, p = 0.012). In contrast, although Media Adoption also had a positive correlation with SME Performance (r = 0.665, p < 0.01), its effect was not statistically significant in the regression analysis (B = 0.250, p = 0.276). ANOVA analysis showed that the regression model as a whole was significant in explaining the variation in SME Performance (F-test significant), with an R Square of 0.478, which means that 47.8% of the variation in SME performance can be explained by this model. The conclusion of this study suggests that customer orientation is a key factor in improving SME performance, while media adoption, while important, requires a more strategic approach to make a significant impact. These findings emphasize the importance of focusing on customer orientation and effective media strategies in the management of SMEs to achieve optimal performance.